FINANCIAL ANALYSIS OF FISHERIES BUSINESS PAYANG IN KM.QUEEN IN PADANG WEST SUMATERA PROVINCE - Cahyo, Deon Dwi; Rengi, Pareng; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study aims to determine the costs, benefits and financial analysis of payang fishing gear at KM Queen which is operated on the Padang coast of West Sumatra Province. The research was conducted in August 2018, at Padang Beach, West Padang, Padang City, West Sumatra Province. The research method used is the survey method. In this research, the collected data consists of primary data and secondary data. The primary data is obtained from direct observation of fishing activities and can also be obtained from ports and local fisheries department. Secondary data was obtained through literature studies and government agencies related to research. During the study it was known that construction of fishing gear on the coast of Padang, Padang City, West Sumatra Province was the same as other regions which had several parts in common, namely bodies, wings, bags, buoys, ballast, and rope. From the results of the financial analysis, the shore at Padang beach was obtained by Benefit Cost of Ratio of 1,07 which means that the BCR value> 1, then this fishery is worthy to continue. Financial Rate of Return is 45,08% so capital should be invested into the business so that it is more profitable. Payback Period of Capital is 2,2 meaning that the time needed by fishermen for capital returns is for 2 years2 months. Keywords: Technical Aspects; Financial Analysis; Payang Fishing Gear; Padang Beach